2017
DOI: 10.1007/s00280-017-3475-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic prediction of treatment outcome in pancreatic ductal adenocarcinoma patients receiving gemcitabine

Abstract: This work established proof-of-principle for GC/TOFMS-based global metabotyping of PDAC and laid the foundation for future discovery of metabolic biomarkers predictive of gemcitabine resistance in PDAC chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…In a prospective cohort study, dietary oleic acid intake was inversely related to the risk of pancreatic ductal adenocarcinoma (significant in patients with a BMI > 25 kg/m 2 ) [25]. Another study using tumor tissues of pancreatic ductal adenocarcinoma patients revealed that oleic acid and stearic acid were significantly higher in the group with favorable survival than in that with low survival [28]. Thus, our HFS might have provided additional benefits to the patients due to the high contents of oleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study, dietary oleic acid intake was inversely related to the risk of pancreatic ductal adenocarcinoma (significant in patients with a BMI > 25 kg/m 2 ) [25]. Another study using tumor tissues of pancreatic ductal adenocarcinoma patients revealed that oleic acid and stearic acid were significantly higher in the group with favorable survival than in that with low survival [28]. Thus, our HFS might have provided additional benefits to the patients due to the high contents of oleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The study was designed to accurately exclude suspected pancreatic cancer in CP patients, with emphasis placed on optimizing the negative predictive value (NPV) [52,53]. In another metabolomic approach, Phua et al established metabotyping of resected PDAC tissue to predict gemcitabine treatment response in an adjuvant setting [54]. This proof-of-principle work showed that distinct tissue metabolomes, consisting of various amino acids, fatty acids, nucleobase intermediates and inorganic acids, could be used to depict the treatment response of gemcitabine [54].…”
Section: Opportunities Of Metabolic Profiles To Develop Targeted Thermentioning
confidence: 99%
“…In another metabolomic approach, Phua et al established metabotyping of resected PDAC tissue to predict gemcitabine treatment response in an adjuvant setting [54]. This proof-of-principle work showed that distinct tissue metabolomes, consisting of various amino acids, fatty acids, nucleobase intermediates and inorganic acids, could be used to depict the treatment response of gemcitabine [54]. The near future probably lies in a carefully selected panel of metabolome biomarkers that would allow for earlier diagnosis of PDAC, an easier determination of its stage and, ideally, provide indicators of prognosis or outcome.…”
Section: Opportunities Of Metabolic Profiles To Develop Targeted Thermentioning
confidence: 99%
“…Indeed, several lines of evidence indicate that metabolic flexibility is an important determinant of resistance to cancer therapies [ 25 ]. There is evidence from metabolomics analysis of tissue in pancreatic ductal adenocarcinoma patients that metabolic biomarkers may be predictive of resistance to the chemotherapy gemcitabine [ 26 ]. Metabolic changes may also be associated with drug-induced toxicity [ 27 , 28 ], suggesting that VOC biomarkers in breath could be explored as potential predictors of toxicity.…”
Section: Precision Medicine Applications For Breath Biopsymentioning
confidence: 99%